ETC antenna (easy to configure): a new approach to smart management of cellular networks (2010)
The ETC antenna is presented as an intermediate approach between the current radio cellular systems and the future cellular system with the smart antennas. The goal is to get a flexible and asynchronous way to optimize the coverage following the schedule traffic changes and the requirements of the cell using the current mobile operator measurements and making the beam changes by a programmatic and remote technique.